Implementing Cooperative Learning for Sustainable STEM Education in Nigeria: Preservice Science Teachers’ Knowledge and Beliefs - Emmanuel Chibuike Nwune; Nnaemeka Kenechi Oguezue; Kingsley Chinaza Nwosu (Scientia Publica Media, 2024)
The study investigated preservice science teachers’ (PST) knowledge and beliefs about the implementation of cooperative learning for sustainable science, technology, engineering, and mathematics (STEM) education in Nigeria given that evidence shows that several Nigerian teachers are still unskilled in 21st-century pedagogies. The study sought to determine PSTs’ competencies for implementing cooperative learning in science classrooms, as informed by their knowledge and beliefs about the effectiveness of applying cooperative learning to teach science concepts. Four research questions guided the study. The design of the study is a descriptive survey involving the collection of quantitative data via questionnaires. This research design is appropriate for the present study as it sought to determine the knowledge and beliefs PSTs have about cooperative learning (CL). The study sample was drawn from all the PSTs in the federal tertiary institution (Nnamdi Azikiwe University, Awka) in Anambra State, Nigeria using the convenience sampling technique. The data for this study were collected electronically using an adapted version of Bouas (1993). The scale’s reliability was determined using the Cronbach alpha technique (α=.73). Percentage, weighted mean, and standard deviation, and one sample t-test were used to analyse the data collected in this study. The study’s findings showed that PSTs in Nigeria were both knowledgeable and held positive beliefs about cooperative learning pedagogy. Based on the study’s findings, implications for the study were discussed.